Integrated academic sport education system to build professional trainer`s motivations: frame model - Mikhaylova, T. V. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to develop and substantiate by an experiment a frame model of an integrated academic sport education system to build professional trainer`s motivations. The study was performed in the period of 2004 through 2016 at the Physical Education and Sports Institute of Russian State University of Physical Education, Sport, Youth and Tourism and a few Russian and Belorussian universities. Subject to the study were 2000 general education school graduates qualified as physical education university entrants and students. The frame motivations-building model was found effective with the relevant educational and psychological tools being combined to build up motivations by due approvals (by compliments, expressed appreciation, trust and support, arguments, explanations, summaries, instructions, proof, disproof, personal examples) and compulsion (reproof, censure, reproach, warning, penalty etc.).